2020
DOI: 10.3390/foods9081071
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Physicochemical Properties of Breadfruit Flour Using Different Twin-Screw Extrusion Conditions and Its Application in Soy Protein Gels

Abstract: The objective was to modify functional properties of breadfruit flours using twin-screw extrusion and test the physicochemical properties of the extruded flours. Extruded breadfruit flours were produced with twin-screw extrusion using different last barrel temperature (80 °C or 120 °C) and feed moisture content (17% or 30%). These conditions resulted in four extruded flours with different mechanical (specific mechanical energy, SME) and thermal (melt temperature) energies. At temperatures below the gelatinizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
1
10
0
2
Order By: Relevance
“…Sakonidou and Huang et al also reported that high temperature weakened the shear hindrance in solution and finally reduced the viscosity. [37,38] The peak viscosity, breakdown, final viscosity, and setback of HARA were greater than those of MRA, which indicated that microwave had a more destructive effect on the internal structure of RA than hot air. In addition, the trough viscosity had no significant difference between HARA and MRA, which indicated that the two drying methods had the same effect on the binding between molecules.…”
Section: Drying Parametersmentioning
confidence: 98%
“…Sakonidou and Huang et al also reported that high temperature weakened the shear hindrance in solution and finally reduced the viscosity. [37,38] The peak viscosity, breakdown, final viscosity, and setback of HARA were greater than those of MRA, which indicated that microwave had a more destructive effect on the internal structure of RA than hot air. In addition, the trough viscosity had no significant difference between HARA and MRA, which indicated that the two drying methods had the same effect on the binding between molecules.…”
Section: Drying Parametersmentioning
confidence: 98%
“…These factors are affected by various extrusion parameters and its intensity which include moisture content, feed rate, temperature of barrel, and screw speed ( 55 ). Extrusion cooking of breadfruit flour has shown to retain its starch and protein content however, a significant decrease in lipid and a significant increase in ash content was observed ( 56 ). Extruded breadfruit flour using low specific mechanical energy highlighted greater water-binding capacity and lower solubility compared to flour extruded using high specific mechanical energy.…”
Section: Breadfruit Pulp Processingmentioning
confidence: 99%
“…Kemampuan adonan dalam mengikat minyak dapat dilihat pada Gambar 8. OHC atau daya ikat minyak bergantung pada gugus hidrofobik pada bahan dan kemampuan bahan mengikat minyak melalui struktur bahan tersebut (Huang, Roman, Martinez, & Bohrer, 2020). Pada Gambar 8 dapat dilihat bahwa daya ikat minyak pada mokaf berbagai perlakuan lebih tinggi dibandingkan kontrolnya (tepung singkong tanpa fermentasi) namun belum dapat dinyatakan bahwa semakin lama waktu fermentasi akan semakin meningkatkan nilai OHC nya.…”
Section: Rapid Visco Amylograph (Rva)unclassified